High prevalence of undisclosed antiretroviral drug use among individuals initiating HIV treatment in Gaborone, Botswana - Moraka, Natasha O.; Moyo, Sikhulile; Mohammed, Terence; Molebatsi, Kesaobaka; Wiesner, Lubbe; Mokgethi, Patrick T.; Gobe, Irene; Mokomane, Margaret; Moutswi, Salang T.; Rabatoko, Laone; Leteemane, Queen; Strachan-Amaro, Vanessa; et al. (Frontiers in Public Health, 2025)
BackgroundAntiretroviral therapy (ART) uptake is critical for evaluating the effectiveness of HIV epidemic control. We evaluated the extent of undisclosed ARV drug use among individuals newly diagnosed and initiating ART in greater Gaborone, Botswana.MethodologyPlasma samples from an ongoing longitudinal cohort study were screened for antiretroviral drug (ARV) traces using the liquid chromatography with tandem mass spectrometry assay. The ARV drug screening panel used detects 4 ARV drugs: Integrase Strand Transfer Inhibitor [INSTI]—dolutegravir (DTG), two non-nucleoside reverse transcriptase inhibitors [NNRTIs]—Efavirenz (EFV), Nevirapine (NVP), and a protease inhibitor [PI]—Lopinavir. We estimated adjusted prevalence ratios (aPR) for factors associated with undisclosed ART use using modified Poisson regression.ResultsWe enrolled 192 participants, between October 2023 and January 2024, and a total of 120 (63.4%) were screened for plasma ARV drug traces. Participants were of median age 32 (IQR 26, 39), mostly female (66.7%) and of Botswana nationality (75.0%). Among those screened for ARV drug traces 36 (30.0%; 95%CI: 30–39) participants had at least one of the ARVs in the panel detected. One participant (0.8%) was positive for EFV, and 35 (29%) had DTG traces at baseline. Undisclosed ART use was associated with lower viral load (aPR = 0.84; 95%CI: 0.70–1.00) and being of non-Motswana nationality (aPR = 2.6; 95%CI: 1.5–4.5).ConclusionWe report a relatively high proportion of individuals with undisclosed drug use in their baseline plasma. Our results suggest the need to implement pre-drug screening for routine HIV incidence surveillance, including pre-treatment drug resistance evaluations before ART initiation.